Evaluasi Usability Terhadap User Interface Aplikasi Medizi Berbasis Website Menggunakan Heuristic Walkthrough - Vera Wati; Hanifah Muslimah Az-Zahra; Niken Hendrakusuma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Medizi is the web based application which enhanced from previous application using another channel called EDC (Electronic Data Capture). This application is used to facilitate the claim process for member of insurance in hospitals or clinic. Along its development, Medizi has never apply the complex evaluation. Therefore the usability evaluation of the user interface of the Medizi was conducted to improve the quality of usability in Medizi. The Heuristic walkthrough method is applied for this evaluation. The Heuristic walkthrough is a combined method between the cognitive walkthrough and heuristic evaluation. This evaluation involves the representative users in domain experts and usability experts that consist of four domain experts and three usability experts. Cognitive walkthrough is the type of evaluation that produce problems in each stage of the task with a throught provoking question as assistance that support by the domain expert and usability expert. Meanwhile the heuristic evaluation is an evaluation that conducted by the usability expert by comparing the applications with heuristic principles and determining the saverity rating value. After the evaluation applied, thirty one cognitive walkthrough problems were found and 38.7% of problems also found in the heuristic evaluations. In the heuristic evaluation, there are twenty problems found with the highest heuristic number on H-4 (consistency and standard) with 30% percentage of the problems found. Considering the results of this evaluation, it figured out the sixteen recommendations for improvement where nine of recommendations are to improve the user interface design and seven of recommendations are for system improvements issue.